Intestinal Malrotation in Children: Clinical Presentation and Outcomes - Salehi Karlslätt, Karin; Husberg, Britt; Ullberg, Ulla; Nordenskjöld, Agenta; Wester, Tomas (European Journal of Pediatric Surgery, 2023)
Introduction Intestinal malrotation (IM) is characterized by abnormal intestinal rotation and fixation predisposing to a risk of midgut volvulus. The aim of this study was to describe the clinical presentation and outcome of IM from birth through childhood.Materials and Methods This was a retrospective study of children with IM managed at a single center between 1983 and 2016. Data were retrieved from medical records and analyzed.Results Three hundred nineteen patients were eligible for the study. Using strict inclusion and exclusion criteria, 138 children were included. Vomiting was the most common symptom up to 5 years of age. At 6 to 15 years of age, abdominal pain was the predominant symptom. One hundred twenty-five patients underwent a Ladd's procedure and of 124 patients with available data, 20% had a postoperative complication (Clavien-Dindo IIIb-V) within 30 days. The odds ratio to develop postoperative complications was significantly increased in extremely preterm patients (p = 0.001) and in patients with severely affected intestinal circulation (p = 0.006). Two patients had intestinal failure due to midgut loss after midgut volvulus, one of whom needed intestinal transplantation. Four patients, all extremely preterm, died related to the surgical procedure. In addition, seven patients died of reasons not related to IM. Fourteen patients (11%) had adhesive bowel obstruction and one patient had recurrent midgut volvulus requiring surgical treatment.Conclusions IM presents with different symptoms through childhood depending on age. Postoperative complications are common after Ladd's procedure, particularly among extremely preterm infants and patients with severely affected circulation caused by midgut volvulus.
Keywords: intestinal malrotation; intestinal rotation abnormalities; malrotation; midgut volvulus